PENGARUH LAMA PENYIMPANAN ADONAN BEKU TERHADAP SIFAT FISIKOKIMIA DAN ORGANOLEPTIK PUFF PASTRY YANG DISUBSTITUSI MODIFIED CASSAVA FLOUR - Mardiah, Afa Dian; Trsinawati, Chatarina Yayuk; Surjoseputro, Sutarjo (Widya Mandala Surabaya Catholic University, 2014)
The use of frozen dough allow to maintain consistency of the product simultaneously. The formula used mocaf flour 15% as wheat substitution. The objective of this research was to study the effect of storage time of frozen dough on the physicochemical properties and sensory as well as how long the maximum storage of frozen dough that can produce puff pastry that can be accepted by consumers. The experimental design of the study was a randomized block design with single factor, which the storage time of frozen dough consist of five levels (0, 5, 10, 15, and 20 days) with five replication. The parameters tested were moisture content, spesific volume, firmness, and sensory properties in firmness, flakiness, moutfeel (greasy texture), and sugar content. The data were analyzed using ANOVA at α = 5% and followed by DMRT (Duncan’s Multiple Range Test) at α = 5% if there was a significant effect of treatment. The frozen storage time significantly reduced water content and specific volume, increased firmness, and panelist acceptance in flakiness. The storage time has no significantly different in sugar content, panelist acceptance in firmness, and mouthfeel (greasy texture).